Glutaminolysis and lipoproteins are key factors in late immune recovery in successfully treated HIV-infected patients. (29th April 2019) - Rosado-Sánchez, Isaac; Rodríguez-Gallego, Esther; Peraire, Joaquim; Viladés, Consuelo; Herrero, Pol; Fanjul, Fran; Gutiérrez, Félix; Bernal, Enrique; Pelazas, Ricardo; Leal, Manuel; Veloso, Sergi; López-Dupla, Miguel; et al.
Abstract : The immunological, biochemical and molecular mechanisms associated with poor immune recovery are far from known, and metabolomic profiling offers additional value to traditional soluble markers. Here, we present novel and relevant data that could contribute to better understanding of the molecular mechanisms preceding a discordant response and HIV progression under suppressive combined antiretroviral therapy (cART). Integrated data from nuclear magnetic resonance (NMR)-based lipoprotein profiles, mass spectrometry (MS)-based metabolomics and soluble plasma biomarkers help to build prognostic and immunological progression tools that enable the differentiation of HIV-infected subjects based on their immune recovery status after 96 weeks of suppressive cART. The metabolomic signature of ART-naïve HIV subjects with a subsequent late immune recovery is the expression of pro-inflammatory molecules and glutaminolysis, which is likely related to elevate T-cell turnover in these patients. The knowledge about how these metabolic pathways are interconnected and regulated provides new targets for future therapeutic interventions not only in HIV infection but also in other metabolic disorders such as human cancers where glutaminolysis is the alternative pathway for energy production in tumor cells to meet their requirement of rapid proliferation.